Antimicrobial resistance : global report on surveillance (World Health Organization, 2014)
This WHO report produced in collaboration withMember States and other partners provides as accuratea picture as is presently possible of the magnitude ofAMR and the current state of surveillance globally. The report focuses on antibacterial resistance (ABR)in common bacterial pathogens. Why? There is amajor gap in knowledge about the magnitude of thisproblem and such information is needed to guideurgent public health actions. ABR is complex andmultidimensional. It involves a range of resistancemechanisms affecting an ever-widening range ofbacteria most of which can cause a wide spectrumof disea.